A mixed splicing procedure for economic time series - Angel de la Fuente (Center for Economic Studies and ifo Institute (CESifo), 2009)
This note develops a flexible methodology for splicing economic time series that avoids the extreme assumptions implicit in the procedures most commonly used in the literature. It allows the user to split the required correction to the older of the series being linked between its levels and growth rates on the basis what he knows or conjectures about the persistence of the factors that account for the discrepancy between the two series that emerges at their linking point. The time profile of the correction is derived from the assumption that the error in the older series reflects the inadequate coverage of emerging sectors or activities that grow faster than the aggregate.
Keywords: C82; E01; 330; linking; splicing; economic series